Peran Kepala Sekolah dalam Peningkatan Mutu Pendidikan Melalui Mutu Proses (Studi di MI Plus Nur Rahma Kota Bengkulu) - Indah Kurnia (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This research aims to determine the role of the school principal in planning, organizing, implementing, and controlling educational programs to improve the quality of education at MI Plus Nur Rahma and to determine the role of the school principal in implementing The principal's management function is to improve the quality of education through process quality at MI Plus Nur Rahma. The type of research that the author used in this research is field research. This research uses a qualitative descriptive approach. The results of this research The role of the principal as a manager is the role of the principal to manage and utilize the educational resources owned by the school by jointly achieving the goals that have been set, with the principal having a solid academic spirit as an educator, having Straightforward communication, having mutually agreed programs and having a fair leadership spirit will support the quality level of the process towards the same goal. Conclusion, The role of the Principal in planning, organizing, implementing, controlling, and evaluating educational programs to improve the quality of education at MI Plus Nur Rahma Keywords: role of school principal, quality of education